2014
DOI: 10.1371/journal.pone.0091502
|View full text |Cite
|
Sign up to set email alerts
|

A New Stochastic Model for Subgenomic Hepatitis C Virus Replication Considers Drug Resistant Mutants

Abstract: As an RNA virus, hepatitis C virus (HCV) is able to rapidly acquire drug resistance, and for this reason the design of effective anti-HCV drugs is a real challenge. The HCV subgenomic replicon-containing cells are widely used for experimental studies of the HCV genome replication mechanisms, for drug testing in vitro and in studies of HCV drug resistance. The NS3/4A protease is essential for virus replication and, therefore, it is one of the most attractive targets for developing specific antiviral agents agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 89 publications
1
3
0
Order By: Relevance
“…While goodness of fit based on cumulative AIC values for the three viruses (electronic supplementary material, table S4) demonstrates only a marginal advantage in favour of our main model, measured CM formation dynamics [33,34] support our choice of the model. Corroboration with independent experimental data like recovery of steady-state levels of replication intermediate [17,59,60] and steady-state positive/ negative RNA ratios [46,47] (electronic supplementary material, table S4) further supports our model. Due to the lack of molecular details for virus assembly, our model only qualitatively captures the virus assembly and release dynamics and we cannot discriminate between alternative sites (CMs versus cytoplasm) for virus assembly.…”
Section: Comparative Analysis Of Monopartite (+)Rna Virusessupporting
confidence: 76%
“…While goodness of fit based on cumulative AIC values for the three viruses (electronic supplementary material, table S4) demonstrates only a marginal advantage in favour of our main model, measured CM formation dynamics [33,34] support our choice of the model. Corroboration with independent experimental data like recovery of steady-state levels of replication intermediate [17,59,60] and steady-state positive/ negative RNA ratios [46,47] (electronic supplementary material, table S4) further supports our model. Due to the lack of molecular details for virus assembly, our model only qualitatively captures the virus assembly and release dynamics and we cannot discriminate between alternative sites (CMs versus cytoplasm) for virus assembly.…”
Section: Comparative Analysis Of Monopartite (+)Rna Virusessupporting
confidence: 76%
“…It is worth noting that the DEEP method was previously successfully applied to several systems biology problems [34,35,36]. The distinctive features of the DEEP method are the flexible selection rule for handling multiple objective functions and substitution strategy that takes into account the number of iterations between updates of each parameter vector.…”
Section: Differential Evolution Entirely Parallel Methodsmentioning
confidence: 99%
“…, their estimated half‐life of intracellular genotype 1b subgenomic replicon RNA was between 16–19 h. However, Ivanisenko et al . showed that the observed bi‐phasic RNA decline can also be explained by the accumulation of drug resistant mutants considering stochastic viral mutation and selection in the previous subgenomic model . Two extensive reviews about viral kinetic modeling in the context of treatment with a specific focus on HCV and influenza virus can be found in and .…”
Section: The Replication Within—intracellular Processesmentioning
confidence: 99%